In the Shadow of the “Indeterminate Speech-Act”: The Populist Politics of Rumor in Fritz Lang’s Early Sound Films - Florian Zappe (European Journal of American Studies)
Based on Gilles Deleuze’s claim that rumor has been a “cinematographically privileged object” in early sound cinema, this essay will provide a political analysis of the representation of rumor in two early sound films in the transnational oeuvre of Fritz Lang. This interpretation of M―Eine Stadt sucht einen Mörder (Germany, 1931) and Lang’s first Hollywood production Fury (USA, 1936) will show that the shift from silent to sound cinema marks not only an aesthetic and technological innovation, but also coincides with an increased political awareness in the director’s oeuvre. While his films of the silent era remain politically ambiguous and have often been accused of foreshadowing fascist themes and aesthetics, the sound films produced shortly before and after Lang’s emigration to the United States take a clear political stand with regards to the toxic effects of rumors as expressions of populist sentiments and, in this, provide a gateway to the director’s integration into American liberalism.